PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BADAN LAYANAN UMUM DAERAH (BLUD) RUMAH SAKIT MAYJEN HM. RYACUDU LAMPUNG UTARA - Ahmad Junaedi (e-JKPP, 2017)
The problem of this research are (1) is there an influence of work motivation toward employees’ work of District General Services at Mayjen HM. Ryacudu Hospital of North Lampung; (2) is there an influence of work discipline toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung; and (3) is there an influence of work motivation and discipline of work toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung.            The objective of this research is to analyze and to know: (1) the influence of work motivation toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung; (2) the influence of work discipline toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung; and (3) the influence of work motivation and the discipline of work toward employees’ work of District General Service at Mayjen HM Ryacudu Hospital of North Lampung.            The hypothesis of this research are:  (1) motivation of work has a positive influence toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung; (2) the discipline of work has a positive influence toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung and (3) work motivation and the discipline of work influential work together toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung.            This research uses explanatory Survey with analyze the influence of work motivation and the discipline of work as independent variables and employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung as dependent variable. The population of this research consists of 575 employees and the sample of this research consists of 58 employees (10%). The technique of collecting data of this research uses questioner, interview, observation, and documentation. The technique of data analysis uses statistic Multiple Linear Regression.            The result of this research indicates that (1) work motivation has a positive influence and significant toward the employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung; (2) the discipline of work has a positive and significant toward employees’ work of District General Services at Mayjen HM Ryacudu Hospital of North Lampung; and (3) work motivation and the discipline of work have a positive influence and significant toward employees’ work of District General Service at Mayjen HM Ryacudu Hospital of North Lampung simultaneously.